2020
DOI: 10.1039/c9sc05311e
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light-induced intramolecular charge transfer in the radical spirocyclisation of indole-tethered ynones

Abstract: Indole-tethered ynones form an intramolecular electron donor–acceptor complex that can undergo visible-light-induced charge transfer to promote thiyl radical generation from thiols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 96 publications
1
57
0
Order By: Relevance
“…[12] Unsworth's group reported a visible-light-induced intramolecular charge transfer in the radical spirocyclisation of indol ynones with thiols leading the formation of 3-thiospiroindolenines under the argon condition, in which an intramolecular EDA complex was formed (Scheme 1b). [13] As our continued interest in visible light photoredox catalysis [14] and the formation of CÀ Se bond, [15] herein, we present an efficient visible-lightpromoted selenylative spirocyclisation of indolyl-ynones to 3selenospiroindolenines at room temperature under air condition (Scheme 1c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12] Unsworth's group reported a visible-light-induced intramolecular charge transfer in the radical spirocyclisation of indol ynones with thiols leading the formation of 3-thiospiroindolenines under the argon condition, in which an intramolecular EDA complex was formed (Scheme 1b). [13] As our continued interest in visible light photoredox catalysis [14] and the formation of CÀ Se bond, [15] herein, we present an efficient visible-lightpromoted selenylative spirocyclisation of indolyl-ynones to 3selenospiroindolenines at room temperature under air condition (Scheme 1c).…”
mentioning
confidence: 99%
“…The irradiation of diphenyl diselenide (2 a) produced phenylselenyl free radicals A. [17] In path a, [13] the addition of indolyl-ynone 1 a with the phenylselenyl radicals A afforded an alkenyl radical B, followed by cyclising with the indole at its 3-position to form a spirocyclic radical intermediate C. Oxidation of C to D in the air atmosphere, which underwent dehydrogenation in the base condition to afford the desired product 3 a. In path b, [18] Oxidation of phenylselenyl radicals A to PhSe + in the air atmosphere, which reacted with the alkyne group of indolylynone 1 a leaded the formation of selenium ion E. Then, the cyclization of E at 3-position of indole to give the desired product 3 a.…”
mentioning
confidence: 99%
“…The authors highlight that this is only the second reported use of intramolecular EDA complexes in the literature, [124] and admit that this rare form of radical activation was uncovered serendipitously. Regioselective addition of the somewhat electrophilic Somewhat analogous to the work reported by the Hong group, a recent report by Ho et al describes an electron-donor-acceptor (EDA) complex which undergoes visible light-induced charge transfer, and facilitates the radical spirocyclization of a number of indole-tethered ynones 307a-j (Scheme 47) [123]. The EDA complex promotes thiyl radical generation and initiates a cascade that features a dearomatizing spirocyclization with concomitant carbon-sulfur bond formation, to yield a number of indolines 308a-j.…”
Section: State Of the Artmentioning
confidence: 85%
“…Somewhat analogous to the work reported by the Hong group, a recent report by Ho et al describes an electron-donor-acceptor (EDA) complex which undergoes visible light-induced charge transfer, and facilitates the radical spirocyclization of a number of indole-tethered ynones 307a – j ( Scheme 47 ) [ 123 ]. The EDA complex promotes thiyl radical generation and initiates a cascade that features a dearomatizing spirocyclization with concomitant carbon-sulfur bond formation, to yield a number of indolines 308a – j .…”
Section: Heterogeneous Substrates: Enynes and Other Mixed Systemsmentioning
confidence: 92%
“…[28b] Meanwhile, a catalyst-free version of the lightinduced intramolecular charge transfer to promote thiyl radical generation from thiols was proposed by Taylor and Unsworth' group in 2020, in which indole-tethered ynones formed an intramolecular electron donor-acceptor complex (Scheme 15c). [29] This work combines the dearomatization of indoles with the radical cascade reaction of ynones, providing a completely new way for the construction of spirocyclic indolines. Mechanistically, a photoexcited state 56 was formed with the absorption of visible light after the intramolecular formation of EDA complex 55.…”
Section: Ipso-annulation Of Ynonesmentioning
confidence: 99%